1991
DOI: 10.1128/jb.173.8.2625-2632.1991
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of spo0A transcription in Bacillus subtilis: glucose represses promoter switching at the initiation of sporulation

Abstract: We have shown by Si nuclease mapping with in vivo transcripts that the differential expression of a sporulation-regulatory gene, spoOA, is regulated by switching of two discrete promoters during the initiation of sporulation in Bacillus subtilis; vegetative mRNA was transcribed from an upstream promoter (Pv, vegetative promoter), and sporulation-specific mRNA was transcribed from the other promoter (Ps, sporulation-specific promoter) about 150 bp downstream of the P, promoter. Transcription from the P, prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 27 publications
2
89
0
Order By: Relevance
“…4). In addition, we found that the expression of spo0A from the Ps promoter, which is recognized by the sporulation initiation sigma factor, s H (Chibazakura et al, 1991;Predich et al, 1992), was hardly detected in the D9 rrnO + strain (data not shown). Also, microscopic observations revealed that most of the mutant cells were blocked at the early stages of sporulation, where no obvious asymmetrical septum was found (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…4). In addition, we found that the expression of spo0A from the Ps promoter, which is recognized by the sporulation initiation sigma factor, s H (Chibazakura et al, 1991;Predich et al, 1992), was hardly detected in the D9 rrnO + strain (data not shown). Also, microscopic observations revealed that most of the mutant cells were blocked at the early stages of sporulation, where no obvious asymmetrical septum was found (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…It is phosphorylated by a complex phosphorelay that includes several components needed to integrate multiple signals [2]. The spoOA gene product regulates negatively the abrB gene [3,4], a repressor of several genes which transcription is initiated during the transition between exponential growth and stationary phase [5]. As a positive effector, Spo0A is indispensable for activating the expression of at least three important stage II genes or operons [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the disappearance of AbrB could not be responsible for stimulating 0A synthesis. To further investigate the role of AbrB, we took advantage of the fact that spo0A is transcribed both from a vegetative promoter (P v ) responsible for 0A synthesis during growth (recognized by σ A ) and a σ H -dependent promoter (P s ) required for sporulation (11). As expected, in a mutant lacking P v , little or no 0A was present during growth, and, as a consequence, AbrB was at higher than normal levels at hour 0 and remained at high levels even at hour 2.…”
Section: Positive Feedback Loop Involving Abrb and σ H Does Not Signimentioning
confidence: 99%